2019
DOI: 10.1136/bmj.l2378
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing financial protection under China’s social health insurance to achieve universal health coverage

Abstract: Hai Fang and colleagues highlight the need for better financial protection for poor people

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 12 publications
1
131
0
Order By: Relevance
“…In 2009, China launched a new comprehensive health system reform, which focused on five areas: service delivery, essential medicines, public health service, social health insurance, and public hospital reform. The Chinese government has implemented a series of measures to ensure the provision of accessible and affordable care to cancer patients and protect their health and wellbeing since the 2009 health system reform [2,3]. Almost the entire Chinese population (more than 95% of total) has been covered by one of three social health insurance programs, including the Urban Employee Basic Medical Insurance (UEBMI) Scheme, the Urban Resident Basic Medical Insurance (URBMI) Scheme, and the New Rural Cooperative Medical Scheme.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, China launched a new comprehensive health system reform, which focused on five areas: service delivery, essential medicines, public health service, social health insurance, and public hospital reform. The Chinese government has implemented a series of measures to ensure the provision of accessible and affordable care to cancer patients and protect their health and wellbeing since the 2009 health system reform [2,3]. Almost the entire Chinese population (more than 95% of total) has been covered by one of three social health insurance programs, including the Urban Employee Basic Medical Insurance (UEBMI) Scheme, the Urban Resident Basic Medical Insurance (URBMI) Scheme, and the New Rural Cooperative Medical Scheme.…”
Section: Introductionmentioning
confidence: 99%
“…A report by the World Bank and the World Health Organization indicated that China secured a high score for essential health service coverage but a low score for financial protection. 34,35 In October 2016, 36 resident basic medical insurance (URBMI), and the rural new cooperative medical scheme (RNCMS), along with private insurance. 37 These insurance schemes covered approximately 95% of the Chinese population, which represents near-universal health insurance coverage in 2011.…”
Section: China's Health Financing Reformmentioning
confidence: 99%
“…Hospital authorities focus on more diagnostic tests to compensate for the loss of income generated from drug markup, 49 resulting in increased OOP payments. 35 A fragmented information system prevents value-based procurement, and the lack of an efficient evaluation and monitoring system weakens evidence-based data preservation. 50 In addition, hospital managers lack the autonomy to accomplish internal transformation (eg, hiring/firing and salary issues).…”
Section: Challenges Remaining In Out-of-pocket Paymentsmentioning
confidence: 99%
“…In China, there were two health insurance schemes designed exclusively for urban residents: Urban Employee Basic Medical Insurance scheme (UEBMI) for the urban employed and theUrban Resident Basic Medical Insurance scheme (URBMI) for the urban unemployed, retired, children and students,who were not covered by the UEBMI [11]. Covering more than 95% of the residents in urban China during the 2013-2016 period, the two schemes covered roughly 750 million, or 54%, of the total Chinese population [12].The basic differences between UEBMI and URBMI are set out in Table 1.UEBMI is funded both by employers (2% of wages) and employees (6% of annual wages) [13], while the revenue for the URBMI is from individual premium contributions and subsides from central and local government.As shown in Table 1, UEBMIprovides better nancial protection and offers a more comprehensive coverage than URBMI, which focuses on inpatient services, catastrophic illness insurance, but withlimited coverage of basic outpatient services [14]. Patients with UEBMI usually utilize more health services and have higher expense than those with URBMI [15].…”
Section: Introductionmentioning
confidence: 99%